BEYOND THE WAR ON TERROR: UNPACKING THE ENDURING CHALLENGES AND OPPORTUNITIES IN US-PAKISTAN RELATIONS FOR REGIONAL STABILITY - Dr. Sapna Mumtaz; Minahil Ilyas; Umama Sumair; Muhammad Junaid Rashid (International Journal of Contemporary Issues in Social Sciences, 2024)
This paper aims to examine unpack the enduring challenges and potential opportunities inherent in this complex US-Pakistan relationship, with a particular focus on its implications for regional stability in South Asia. The US-Pakistan relationship has undergone significant transformations since the initiation of the War on Terror. While counterterrorism cooperation has been a central pillar, it has also been accompanied by tensions and misunderstandings. Therefore, this research study utilizes a qualitative research methodology, employing both descriptive and analytical approaches, to examine the evolving dynamics of US-Pakistan relations within a case study framework.The study suggests that in the US-Pakistan relationship, persistent challenges include trust deficit, differing strategic priorities, and divergent perceptions of threat assessments. Pakistan’s concerns over US withdrawal from Afghanistan and its implications for regional security exacerbate these challenges. However, there are also opportunities for cooperation. The shared interest in countering terrorism and promoting regional stability provides a foundation for dialogue and collaboration. Additionally, economic engagement, people-to-people exchanges, and a focus on shared values can foster trust and understanding. By navigating these complexities and capitalizing on opportunities, US-Pakistan relations can contribute to a more stable and prosperous region. However, the study recommends that US and Pakistan must navigate their complex relationship by continuing US assistance while respecting Pakistan’s sovereignty, addressing US concerns about terrorism, and collaborating on economic development and regional stability to foster a more peaceful and prosperous future.